How to capitalise on a tribe - Silva, Susana Costa e (2016)
This paper attempts to extend the emergent literature on consumer tribes, in order to provide firms with a more complete understanding of this phenomenon. The main purpose of the study is to identify the existence of tribal behaviour, as well as to propose a model that could guide brands in the identification of tribal bonds. The research is approached interpretively with a case-study investigation of the Prius (Toyota’s hybrid car) tribe. Four different levels of involvement in a consumer-brand relationship are proposed, “tribal” being the most desirable level for a brand to achieve. We also suggest some ways for firms to develop their tribes, and to benefit from that relationship.